Perilaku Radikalisasi Beragama masa Pandemi COVID 19 di Provinsi Jambi - Yanto, Fridi; Amrullah, M. Kholis; Rafi'i, Muhammad; Sobri, Muhammad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2021)
This article examines how COVID-19 Pandemic to be a moment for Islamist group in radicalizing the communities. In many studies have explained that Islam Defend Movement 212 as the biggest moment for Islamism arising. Post 212 movement there was no significance issue to trigger the society. Therefore COVID 19 Pandemic to be islamism consolidation that actually has been fragmented. This reserach used netnography method where the researcher make digital world to be a field of research. Data was collected by observing communities in Facebook groups managed and commented on by the Jambi community. Data was also obtained by collecting online news in Jambi Province. In addition, to add data, the researcher conducted in-depth interviews with 10 informants. Then the reseracher interpreted the symbols, images, and communication patterns that took place in the Facebook group and online media. Furthermore, the data is displayed, analyzed and concluded with the stages carried out in netnographic research. Research findings that COVID 19 Pandemic was capitalised for “anti China” issues and to be a tool to criticise Joko Widodo government because his policy about social distancing has been limited Muslim rituals out of home. The research analysis that COVID 19 Pandemic has been a significance momentum to nurture and to consolidate Islamist group who have experienced at least the issues and the stage for taking action and preserving the views of Islamism. This article discusses that the COVID-19 Pandemic as a curriculum for internalizing Islamism will become a social capital to realize the ideological agendas of radical groups.